CHRONIC PELVIC PAIN SYNDROME – MODERN LOOK TO THE PROBLEM - S. B. Izvozchikov (Klinicist, 2014)
The main causes of chronic pelvic pain syndrome (CPPS), and its pathogenetic mechanisms are described. The criteria of evaluation ofchronic pelvic stress pain are described .It is proposed to use ultidisciplinary approach for therapy CPPS with compulsory neurologists, chiropractic physicians, psychiatrists and therapists, urologists, gynecologists and proctologists involvement to improve diagnostic and quality of therapeutic measures.